2020
DOI: 10.1101/2020.02.10.20021832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of lymphocyte subsets and cytokines in peripheral blood of 123 hospitalized patients with 2019 novel coronavirus pneumonia (NCP)

Abstract: 35Background: To explore the cellular immunity and cytokines status of NCP patients and to predict 36 the correlation between the cellular immunity levels, cytokines and the severity of patients. 37Methods: 123 NCP patients were divided into mild and severe groups. Peripheral blood was 38 collected, lymphocyte subsets and cytokines were detected. Correlation analysis was performed on 39 the lymphocyte subsets and cytokines, and the differences between the indexes of the two groups 40 were analyzed. 41Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
587
1
29

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(644 citation statements)
references
References 2 publications
27
587
1
29
Order By: Relevance
“…Chaolin Huang et al confirmed the occurrence of the J o u r n a l P r e -p r o o f cytokine storm in the COVID-19 patients in ICU rather than those in non-ICU patients [7]. Based on the excessive cytokines responses, Suxin Wan et al claimed that IL-6 and IL-10 levels could be used as one of the bases for predicting the outcome and prognosis of the COVID-2019 [20]. In this study, host cells infected with HCoV-229E and SARS-COV-2 increased the cytokine release such as TNF-α, IL-6, CCL-2/MCP-1, and CXCL-10/IP-10, which was suppressed by LH in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Chaolin Huang et al confirmed the occurrence of the J o u r n a l P r e -p r o o f cytokine storm in the COVID-19 patients in ICU rather than those in non-ICU patients [7]. Based on the excessive cytokines responses, Suxin Wan et al claimed that IL-6 and IL-10 levels could be used as one of the bases for predicting the outcome and prognosis of the COVID-2019 [20]. In this study, host cells infected with HCoV-229E and SARS-COV-2 increased the cytokine release such as TNF-α, IL-6, CCL-2/MCP-1, and CXCL-10/IP-10, which was suppressed by LH in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Cytokine release syndrome is a vital factor that aggravates disease progression. A higher levels of IL-6 and IL-10, and lower levels of CD4+T and CD8+T are observed in COVID-19 patients parallel with the severity of the disease [40].…”
Section: Clinical Characteristics Of Sars-cov-2 Infectionmentioning
confidence: 90%
“…One study analyzed the lymphocyte subsets and cytokines in 123 patients, all patients had ly mphcytopenia, The percentage of CD8 + T cell reduction were 28.43% and 61.9% in mild and severe group respectively, and the NK cell reduction were 34.31% and 47.62% respectively ,in mild and severe groups. Also, serum IL-6 levels in severe group were significantly higher than that in mild group [9]. In addition, the expression of HLA-DR in CD4 + and CD8 + cells was increased, CD4 + CCR4 + CCR6 + Th17 cells also increased, and the cytotoxic particles such as perforin and granolysin were highly expressed in CD8 + T cells [10].…”
Section: Inflammatory Cytokine Storm Was Very Common In Patients Withmentioning
confidence: 93%